2022
DOI: 10.1108/dlp-03-2022-0025
|View full text |Cite
|
Sign up to set email alerts
|

Marketing of library resources and its impact on the library usage of distance-learning students

Abstract: Purpose Access to learning resources in higher education is a prerequisite for effective learning. The purpose of this study is to investigate how marketing of library resources can influences library usage of students from the University of Education Winneba and University of Cape Coast in Ghana. Design/methodology/approach The study was grounded in the pragmatic paradigm and guided by the mixed methods research approach. The sequential explanatory design was used in that, quantitative data was collected fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Students and professionals are encouraged to continuously update their knowledge and skills, keeping pace with the evolving landscape of Information, Library and Archival Studies. The high usage rate of information resources provided by university libraries showcases their importance in enhancing educational and professional programmes (Atuase & Maluleka, 2023). The availability of a diverse collection of books, journals, databases, digital collections and archival materials supports learning, research and professional development, enabling students and professionals to stay informed, contribute to knowledge and excel in their respective endeavours (Keene, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students and professionals are encouraged to continuously update their knowledge and skills, keeping pace with the evolving landscape of Information, Library and Archival Studies. The high usage rate of information resources provided by university libraries showcases their importance in enhancing educational and professional programmes (Atuase & Maluleka, 2023). The availability of a diverse collection of books, journals, databases, digital collections and archival materials supports learning, research and professional development, enabling students and professionals to stay informed, contribute to knowledge and excel in their respective endeavours (Keene, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Clark (2021) demonstrated that marketing can increase the visibility of various library services. In particular, marketing seeks to create relationships with target users by enlightening them about the organization and making patrons conscious of the importance of the library's products and services (Atuase and Maluleka, 2023). A successful marketing strategy also recognizes how an organization's competitors can fluctuate from similar organizations to anything that the target patron chooses to do instead of pursuing the offer, and that competition can be characterized by cooperative and benign relationships that organizations develop with one another (Muneja, 2023).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Non-printed materials are becoming more common, and electronic resources are a growing concept. Strategies and methods such as Digital Marketing (DM) have made it possible to promote the optimal use of library resources (Atuase and Maluleka, 2023). DM platforms and social media have become the most whispering, interactive and critical of all contemporary marketing strategies.…”
Section: Introductionmentioning
confidence: 99%